Janus MoWN MXene with tunable functional groups: Structural stability, mechanical property, and phonon-mediated superconductivity - Sirinee Thasitha; Thiti Bovornratanaraks; Komsilp Kotmool (Journal of Applied Physics, 2025)
Exploring 2D materials has garnered significant attention due to their exceptional physical and chemical properties, making them highly promising for advanced technological applications. Among these, Janus MXenes have emerged as a versatile class of materials with tunable properties. In this work, we theoretically investigate the structural, mechanical, and electronic properties of Janus MoWN MXene structures in both 1T and 2H phases, with particular emphasis on the influence of surface functional groups (Tx). First-principles calculations reveal that the 2H phases are energetically more stable than their 1T counterparts, with MoWNO2 exhibiting the highest stability due to strong Mo–O and W–O bonding interactions. Mechanical analysis indicates that oxygen functionalization significantly enhances the elastic properties of Janus MoWN, whereas fluorine and chlorine terminations do not induce dynamic stabilization. Interestingly, both 2H- and 1T-MoWNO2 phases exhibit metallic behavior, motivating further exploration of their superconducting properties. Electron–phonon coupling analysis using the Eliashberg spectral function reveals a predicted superconducting critical temperature (Tc) of 12.0 K for 1T-MoWNO2 and 2.7 K for 2H-MoWNO2, highlighting the role of structural phase in superconducting performance. We further discuss the electronic states at the Fermi level and the magnitude of Fermi velocity to support the observed electron–phonon coupling strength. Our findings provide new insights into Janus MoWN MXenes and establish their potential for a wide range of future applications, particularly in superconductivity and next-generation electronic devices.
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Boron and Carbon Nanomaterials Research